Synthesis, characterization and application of hydroxyapatite in dental resin - Souad, DARRADJI; Maroua, NEDJIMA (My University, 2022)
Dentistry has recently witnessed a great development, by developing or replacing traditional methods with more advanced and safer methods for human health, including replacing amalgam with resin, because the amalgam contains toxic mercury. The resin prepared in our laboratory contains an organic phase consisting of TMPTMA as a monomer, DMAEMA as a catalyst, DEGDMA as a diluent, CQ as a photocatalyst and hydroxyapatite as a mineral phase. It is obtained in teflon autoclave for heat treatment, and we have adopted bovine bone as a natural source of hydroxyapatite. In order to know the best way to obtain hydroxyapatite closest to the natural source, FR-IR spectroscopy was used and the results were compared. The hydroxyapatite obtained from the two previous methods was taken and mixed in different proportions with the organic phase and exposed to visible light for photo-polymerization and resin formation. FR-IR spectroscopy was used, to find out the optimum ratios of each of the organic and metal phases to form the resin. X- rays were used to study the crystal structure of each of the hydroxyapatite obtained . To study the effect of polymerization time on the degree of polymerization, a mixture of organic phase and metal phase was exposed to different times of visible light and analyzed spectroscopically by FR-IR spectroscopyشهد طب األسنان في الآلونة األخيرة تطورا كبيرا، و ذلك بتطوير أو بإستبدال طرق تقليدية لطرق أكثر تطورا و أمنا على صحة اإلنسان، منها إستبدال الملغم بالراتنج و ذلك إلحتواء الملغم على مادة الزئبق السامة. يحتوي الراتنج المعد في مخبر من طور عضوي مكونة من TMPTMA كمونومير، DMAEMA كمحفز، DEGDMA كمخفف, CQ كمحفز ضوئي و hydroxyapatite كطور معدني تم تحضيره بطريقتين األولى الترسيب التي أستخدم فيها قشور بيض دجاج كمصدر طبيعي للكالسيوم، و الثانية هي الطريقة الحرارية و ذلك بوضع hydroxyapatite المتحصل عليه في autoclave teflon لتلقي معاملة حرارية. إعتمد عظام البقر كمصدر طبيعي لل Hydroxyapatite . من أجل معرفة أفضل طريقة للحصول على hydroxyapatite األقرب للمصدر ال طبيعي. تم إستخدام مطيافية تحت الحمراء IR-FR وXRD و مقارنة النتائج المتحصل عليها. تم أخذ كل من ال hydroxyapatite المتحصل عليه من الطريقتين السابقتين و مزجه بنسب مختلفة مع الطور العضوي و تعريضها للضوء المرئي لحدوث بلمرة ضوئية و تشكيل الراتنج تم إستخدام التحليل الطيفي IR-FR, لمعرفة النسب المثلى لكل من الطور العضوي و المعدني لتشكيل راتنج . لدراسة تأثير زمن البلمرة على درجة البلمرة تم تعريض مزيج من الطور العضوي إلى أزمنة مختلفة من ضوء المرئي و تحليلها طيفيا بواسطة مطيافية تحت الحمراء IR-FR . تم إستخدام األشعة السينية لدراسة البنية الكريستالية لكل من hydroxyapatite المتحصل عليه من طريقة الترسيب بإستعمال بيض دجاج كمصدر للكالسيوم و المتحصل عليه بالطريقة الحرارية .
mémoire master chimie
Keywords: dental resin, Hydroxyapatite, photo-polymerization, teflon autoclave, chicken eggshells.; راتنج األسنان, Hydroxyapatite ,بلمرة الضوئية, autoclave Teflon , بيض الدجاج